Politik Etis dan Dampaknya terhadap Perubahan Sosial di Bandung, 1901-1942 - Muhamad Satria Nugraha; Reiza D. Dienaputra; Risa Junita Sari (Forum for Social and Humanities Studies, 2026)
The objective of this research is to explain the socio-political aspects of Bandung during the Dutch colonial era. Historical research methods, including heuristics, criticism, interpretation, and historiography, support the historical review in this research. The study of social conditions in Bandung, viewed from a temporal perspective before the ethical politics, shows that social life in Bandung was relatively stable and cooperative with the Dutch government. Social conditions in Bandung began to develop dynamically when ethical politics were implemented, and educational freedom was granted. Bandung is one of the regions with quite comprehensive educational facilities from elementary to higher education. The existence of this education gave rise to an educated class and led to the formation of various organizations that influenced socio-political life. Some of these organizations are the Indische Partij, PNI, Sekar Rukun, Paguyuban Pasundan, NU, Muhammadiyah, and Sarekat Islam. These organizations arose from the existence of education and also influenced the struggle through education for subsequent generations. The dynamics of changing social conditions are quite significant, from passivity to active participation in the fight for national independence. The struggles in Bandung were not limited by social, political, or religious status. All organizations played a significant role in the struggle for national independence from Dutch colonial rule. The struggle did not cease even when several prominent figures were imprisoned. Support for the struggle spread from individuals to families, then to society.